Pengaruh Kepemimpinan Terhadap Kinerja Pegawai Unit Pelaksana Teknis Dinas Pendapatan Dan Pengelolaan Keuangan Daerah Di Rangkasbitung - Wildan .; Nenden Pertiwi; Zakiyya Tunnufus (E-Journal Studia Manajemen, 2014)
The purpose of this research was to examine empirically the effect between leadership on job performance among the employees at Technical Implementation Unit Department of Revenue and Fiscal Management in Rangkasbitung. The subjects of this research were 40 employees selected as samples from the overall population of 64 employees. The data of each variable were collected separately by the respondents’ filling in a questionnaire. The effect technique was applied to analyze the data which had been previously treated with the regressive and correlation procedure. The result proved that the employees’ job performance was positively affected by the leadership in Technical Implementation Unit Department of Revenue and Fiscal Management in Rangkasbitung. The findings suggest that the variation of the job performance of the employees might have been affected by leadership.